Critical Legal Analysis of Criminalization Against Environmental Activists in Indonesia - Tengku Ismail Rohmat; Sascia Adelia Putri Wardhani (JUSTISIA GLOBAL EDUKASI, 2026)
Environmental activists play an essential role in promoting ecological protection, community rights, and governmental accountability. However, environmental advocacy in Indonesia is increasingly accompanied by legal actions that allegedly criminalize activists and restrict civic participation. This study critically analyzes the phenomenon of criminalization against environmental activists in Indonesia through the framework of Critical Legal Studies. Using a normative and critical legal methodology, the research examines legal provisions, law enforcement practices, and judicial processes associated with environmental activism. The findings reveal that criminalization frequently occurs through the strategic use of defamation laws, public order regulations, and other legal instruments that may be interpreted broadly against individuals and groups challenging powerful economic interests. Such practices create a chilling effect on public participation and undermine democratic engagement in environmental governance. The study further demonstrates that law is not always applied as a neutral mechanism for dispute resolution but can function as an instrument of power that reinforces existing social and economic hierarchies. The unequal distribution of legal resources and political influence often places environmental activists in vulnerable positions when confronting state institutions or corporate actors. The research argues that stronger legal safeguards are necessary to protect environmental defenders and ensure meaningful public participation in environmental decision-making. The study concludes that the criminalization of environmental activism reflects broader tensions between economic development, environmental protection, and democratic freedoms. These findings contribute to critical legal debates concerning the role of law in shaping power relations and the protection of civil society within Indonesia’s environmental governance framework.